Enhancement Students’ Discussion Activity Through Student Teams Achievement Division (STAD) Co-operative Learning Models with Students’ Worksheet - Rohmadi, Tri; Dwiastuti, Sri; Rosyidi, Alvi (BIO-PEDAGOGI, 2013)
The purpose  of this research  to  enhance  students discussion  activity  by using  of  STAD (Student Teams Achievement Division) learning method with worksheets in class XI IPA 1 SMAN 5 Wonogiri 2008/2009 school year. Kind  of  this research  is  a classroom action research  with  the design consisted  of  two  cycles and each cycle consists  four stages  includes planning, action,  observation  and reflection. The  research subject was  XI IPA  5  class students of SMAN 1 Wonogiri of 2008/2009 school year. Data collection carried out by observation, questionnaires and interviews. Analyzing data in this research is using  qualitative analysis techniques, which refers to the  interactive  analysis model, consists of data reduction, data presentation and drawing conclusions. The validation of the data uses triangulation technique. The results of  first cycle  showed  students  discussion activity  there has been  an increased in  but  not optimized  and  continue in  second  cycle  until the target of  students  discussion activity  has been  optimal  reached.  Based  on the research it can  be  concluded  application  of the  STAD (Student  Teams Achievement  Division) learning method  with worksheets to improving student activity in the discussion, especially biology in class XI IPA 1 SMAN 5 Wonogiri 2008/2009 school year. Key Words: discussion activity, Student Teams Achievement Division